PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI SUMBER BELAJAR GUNA MENINGKATKAN HASIL BELAJAR SISWA PADA MAPEL PENDIDIKAN AGAMA ISLAM DI SD NEGERI 13 PENUKAL UTARA DESA TEMPIRAI TIMUR KECAMATAN PENUKAL UTARA KABUPATEN PENUKAL ABAB LEMATANG ILIR - Nina Septika (UNISAN JURNAL, 2023)
This study discusses the use of information technology as a learning resource to improve student learning outcomes in Islamic religious education subjects at SD Negeri 13 Penukal Utara. The focus of this research is on matters relating to how to use information technology as a learning resource to improve student learning outcomes in the Islamic religious education subject at SD Negeri 13 Penukal Utara. The data collection techniques used were interviews, observations, and documentation of the SD Negeri 13 Penukal Utara agencies in the use of information technology as a learning resource in order to improve student learning outcomes in Islamic religious education subjects at SD Negeri 13 Penukal Utara.The data were obtained by means of observation, direct interviews, and documenting, Islamic religious subject teachers and students, teachers have used information technology as a learning resource, namely learning by using information technology that is available at school as a learning tool, such as laptops, internet, LCDs, and projector.The results showed that. First, the use of information technology in Islamic religious subjects, teachers use learning by using existing technological equipment such as laptops, LCDs, power points, and the internet. Through information technology, students easily accept the material presented by the teacher and students’ learning activities in the classroom are more active, the classroom atmosphere is conducive so that learning will be more effective and efficient and does not look monotonous. Both teachers can use information technology because they want to grow their students’ enjoyment of Islamic religious subjects. It is proven that students who receive material by seeing and hearing will always remember it, understand and know. Therefore, there is a special interest from students in learning Islamic religious education so that it will be easy to absorb the material because of the high enthusiasm of students in learning.These findings can contribute to teachers in choosing appropriate learning resources and in accordance with learning objectives, subject matter, student conditions, available facilities and infrastructure and teacher abilities, so as to create effective learning in order to achieve the expected goals.